The Role of Bureaucratic Structure in the Implementation of The Domestic Wastewater Management Policy in Makassar City - Indriati Amirullah; Nurasia Natsir; Siti Zaleha Soebarini (International Journal of Economics and Management Research, 2024)
This research aims to understand the role of bureaucratic structure in implementing public policy, specifically in domestic wastewater management in Parang Tambung Subdistrict, Tamalate District, Makassar City. The study finds that implementing this policy requires effective coordination among all bureaucratic elements and the involvement of various work units. This research also indicates that the application of Standard Operational Procedures (SOP) and Fragmentation, as Edward C. George III explained, can be effective methods to enhance the success of policy implementation. However, to achieve success in policy implementation, the involvement of all bureaucratic elements and cooperation with external elements is necessary. In conclusion, an effective and efficient bureaucratic structure is crucial for the success of public policy implementation.